Student understanding of science process skills in the implementation of primary science curriculum based on classroom assessment - Abu Bakar, Nuraini (2022)
To succeed in an increasingly technological and advanced world, children must be scientifically literate. Therefore, the science curriculum is designed to provide students with science knowledge so that they can become scientifically literate individuals. Scientific Process Skills (SPS) are required to find answers to problems or systematically make decisions. The SPS can be categorized into basic SPS and integrated SPS (Aydodu et al., 2012; Derilo, 2019; Joseph et al., 2017; Kızılaslan, 2019). Nevertheless, it has been found that the SPS achievement of primary school students remains unsatisfactory. Some of the science teachers show no willingness to teach SPS in class and some of them failed to include all twelve SPS during science lessons. This study focuses on the understanding of students’ SPS via the implementation of a science curriculum in elementary school based on classroom assessment. Data were gathered from six teachers and twelve fifth-grade students selected purposively. The triangulation for a qualitative method is employed and analysed using NVIVO 12 Plus software. Key thematic findings show how students developed their understanding of six basic SPS, six integrated SPS, and basic SPS from prior knowledge. Other themes related are students’ favourite SPS topic that makes students show more interest in developing full comprehension of SPS learning. The study was able to gain some perceptions of the teachers about the students' achievement level in SPS, gathered from teacher’s professional judgment during the classroom assessment. Some issues such as the method, criteria, teaching approach, and teachers' collaboration in assessing students SPS are explained and elaborated accordingly. All the identified themes were validated using Cohen's Kappa calculation. It was found that pupils’ understanding shows a moderate level for basic SPS and low level for integrated SPS. Some of the pupils having little misconception for certain skills such as making inference, while most of them having difficulties to understand and interpreted the integrated SPS. The dominant skill practised by pupils is observation skill, based on the most favourite, easiest and frequency of using SPS. These findings are supported by teachers view that find out the performance of some pupils is at moderate level for basic and integrated SPS. While the performance of the rest is still low and need guidance from teachers according to their cognitive learning level in science. Besides that, the teacher’s view for the pupil’s SPS performance are balance considering the understanding of lower and higher achievement in science. The teachers agreed that both category of pupils has their strength and interest in mastering the SPS. Therefore, it is essential for teacher to use the suitable approach to trigger the pupils’ interest and make the lesson meaningful. The findings also suggest that students need to be engaged in more hands-on activities with greater relevance to SPS. However, the research findings of the pupil’s SPS understanding that infused in the classroom assessment has provide a lot of information to the pupil’s insight learning and for the teachers to modify their instructions. Teachers will be better positioned to modify their instructional strategies and content emphasis to help optimise pupil learning as they become more aware of their pupils' desires, needs, strengths, and weaknesses. When the planning of the pupil’s learning is well strategized, it will give a big impact to the successful implementation of primary science curriculum.